Toward sustainable phycocyanin production using halo-alkaliphilic cyanobacteria: from direct air capture of carbon dioxide to biorefinery - Yi, Lianchun; Solanki, Ruchita; Moll, Miranda; Vadlamani, Agasteswar; De la Hoz Siegler, Hector; Strous, Marc (Frontiers in Microbiology, 2025)
Phycocyanin is a natural blue pigment from cyanobacteria such as Limnospira platensis, also known as “Spirulina.” Its production is costly and faces sustainability challenges due to water needs, carbon dioxide emissions, and lack of operational stability. Here, we review the use of halo-alkaliphilic cyanobacteria to overcome these challenges. This review synthesizes conceptual innovations that were proposed and tested experimentally previously, resulting in the presentation of a complete bioprocess for phycocyanin production. These innovations are: (1) the use of a pH above 10.5 to implement direct air capture of carbon dioxide, reducing carbon dioxide emissions; (2) the use of a consortium of an alkaliphilic cyanobacterium and its associated heterotrophs for improved process stability; (3) the use of passive fermentation for phycocyanin extraction, thereby reducing water needs; and (4) the use of anaerobic digestion to recover energy and recycle carbon dioxide and nutrients. Integrating the above approaches could offer a potentially scalable, more sustainable alternative to conventional phycocyanin production, aligning with circular bioeconomy goals. Several challenges still require solutions. For example, despite water savings, water losses associated with direct air capture of carbon dioxide remain high, and nutrient recycling is only partially successful so far.